Socially responsible human resource practices to improve the employability of people with disabilities. (6th May 2019) - Kwan, Chi Kin
Abstract: Although the employment of people with disabilities (PWDs) has been recognized as an important human right, it is seldom emphasized in current corporate social responsibility (CSR) practice. Based on experiences with a job training program in hospitality for people with intellectual disabilities or Down syndrome offered by a hotel in Hong Kong, this paper explores how socially responsible human resource (HR) practices can support the employment of PWDs. An A‐B‐C‐D framework is proposed by the author to explore what business enterprises can contribute through HR strategy. Based on the results of interviews conducted with the hotel staff and social workers involved in the program, this study suggests that socially responsible HR practices can play an important role in improving the employability of PWDs by providing workplace accommodations, business‐oriented settings, a caring attitude, and job demands, showing how CSR and PWD employment are intertwined.